Can a building social capital intervention improve the mental health of international students? A non-randomized quasi-experimental study. (September 2019) - Khosravi, Roghayeh; Azman, Azlinda; Ayasreh, Emad Abdallah Mustafa; Khosravi, Sahar
Many empirical studies related to social capital have established that there is a relationship between social capital and mental health. However, little research has been conducted to evaluate interventions designed to improve the level of social capital and evaluate its impact on the mental health of international students. This research, applying a quasi-experimental nonequivalent groups design, aimed to address the gap by examining whether an intervention aimed at building social capital can improve social capital and the mental health of international students at Universiti Sains Malaysia. Study findings revealed that the intervention was effective in developing social capital and improving the mental health of international students.